CHILDREN IMITATION ON DAILY LANGUAGES FAMILY COUNSELING PERSPECTIVE - Astri Delia Razi; Mawardi Siregar; Zulkarnain Zulkarnain (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2018)
Humans learn differently. One way humans learn is to imitate (imitation). A child will imitate both parents and learn their habits and behavior patterns. Humans will learn many behaviors and habits in the early phases of his life by imitating his parents, older brothers, brothers and relatives around him. The position of the family in the development of the child's personality is very dominant. The family is a